PENINGKATAN KUALITAS PENDIDIKAN DI INDONESIA; ANTARA CITA DAN FAKTA - Subur Subur (INSANIA : Jurnal Pemikiran Alternatif Kependidikan, 2012)
Abstract : Many issues related to the dynamics of education in Indonesia, which all it really comes down to one goal that is the great hope will be the realization of output quality education. To achieve this, various policies have been issued by either government related educator (certified), learner (model evaluation / UAN), the education process and substance of education itself (caracter building). Policies that too (although we believe well-intentioned) can not be separated from public attention, both the pros and the cons, because it is normal that people give different responses to these policies with their respective arguments. Various policies which have created over the pros and cons deserve identified and examined in depth, it takes clear thinking, rapid, precise, and accurate way to find the best solution in solving various problems that occur. Key Words: Policies, Certification, Exam.